The Effectiveness of Productive Zakat Distribution to Providing Sustainable Benefits for Mustahik in Sungai Penuh City - Helfenta Helfenta; Rahmat Fauzi; Lovi Restiani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Productive zakat is the allocation of zakat money to beneficiaries (mustahik) which is used to develop their business to meet their daily needs sustainably and is not directly used for consumption needs. The problem in this research is how the productive zakat distribution in BAZNAS Sungai Penuh City? Has the distribution productive zakat in BAZNAS Sungai Penuh City been effective? and has the distribution of productive zakat in BAZNAS Sungai Penuh City provided sustainable benefits for mustahik? On the previous studies, researchers only measured the level of effectiveness, while in this study productive zakat is said to be effective if it can provide sustainable benefits for its recipients. This research uses quantitative and qualitative methods. The quantitative method uses the allocation-to-collection ratio to measure the productive zakat distribution. While the qualitative methods uses an interview. The object used in this study is the BAZNAS Sungai Penuh City financial statement from 2019 to 2023. The result of this study indicates that the effectiveness of productive zakat distribution in BAZNAS Sungai Penuh City continues to decline from 2019 to 2023 in a very effective category, but decreasing to quite effective with an ACR percentage of 132% – 53,8%. It can be concluded that mustahik still felt the sustainability of the benefits of the productive zakat program business capital assistance provided by Baznas Sungai Penuh City. In the research data, it can be concluded that Mustahik continues to benefit from the zakat assistance provided by BAZNAS Sungai Penuh City until now.